Glycoproteins From Rabdosia japonica var. glaucocalyx Regulate Macrophage Polarization and Alleviate Lipopolysaccharide-Induced Acute Lung Injury in Mice via TLR4/NF-κB Pathway - Ren, An-qi; Wang, Hui-jun; Zhu, Hai-yan; Ye, Guan; Li, Kun; Chen, Dao-feng; Zeng, Tao; Li, Hong (Frontiers in Pharmacology, 2021)
Abstract Background and Aims: Rabdosia japonica var. glaucocalyx is a traditional Chinese medicine for various inflammatory diseases. This present work aimed to investigate the protective effects of R. japonica var. glaucocalyx glycoproteins against lipopolysaccharide (LPS)-induced acute lung injury (ALI) and the potential mechanism. Methods: The glycoproteins (XPS) were isolated from R. japonica var. glaucocalyx and homogeneous glycoprotein (XPS5-1) was purified from XPS. ANA-1 cells were used to observe the effect of glycoproteins on the secretion of inflammatory mediators by enzyme linked immunosorbent assay (ELISA). Flow cytometry assay, immunofluorescence assay and Western blotting analysis were performed to detect macrophage polarization in vitro. The ALI model was induced by LPS via intratracheal instillation, and XPS (20, 40 and 80 mg/kg) were administered intragastrically 2 h later. The mechanisms of XPS against ALI were investigated by Western blots, ELISA and immunohistochemistry. Results: In vitro, XPS and XPS5-1 down-regulated LPS induced pro-inflammatory mediators production including tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), IL-6 and nitric oxide (NO), and up-regulated LPS induced IL-10 secretion. The LPS stimulated macrophage polarization was also modulated from M1 to M2. In vivo, XPS maintained pulmonary histology with significantly reducing protein concentration and numbers of mononuclear cells in bronchoalveolar lavage fluid (BALF). The level of IL-10 in BALF was up-regulated by XPS treatment. The level of cytokines including TNF-α, IL-1β and IL-6 was down-regulated. XPS also decreased infiltration of macrophages and polymorphonuclear leukocytes (PMNs) in lung. XPS suppressed the expression of key proteins in TLR4/NF-κB signal pathway. Conclusions: XPS was demonstrated to be a potential agent for treating ALI. Our findings might provide evidence supporting the traditional application of R. japonica var. glaucocalyx in inflammation-linked diseases.